Determinants of private savings in the form of bank deposits: A case study on regions of the Russian Federation - Marina Malkina (Economies, 2019)
The paper is aimed at investigating the factors affecting the level of private deposits in banks in Russian regions and the verification of various theoretical concepts of personal savings. To achieve this purpose, we built a set of alternative Cobb-Douglas-type regressions with fixed time effects and logistic-type regressions based on panel data of 80 Russian regions from 2014-2016. Their estimations allowed us to reveal the dependence of private deposits in Russian regions at the level of real personal income and its structure, the personal income inequality, the demographic structure of the population, the state of the labor market, the level of accumulated wealth, the rate of urbanization, and the level of development of the financial system in the regions. Signs with variables summarize both direct and indirect effects of the input variables on the deposits, confirming some theoretical concepts and rejecting others, while the calculated elasticities show the strength of these effects. The results we obtained are applicable to the management of financial resources in Russian regions and the smoothing out of interregional differences in their development.
Keywords: 330; population's savings; private deposits in banks; determinants; characteristics of population; wealth effect; econometric modeling